Masonry bond by using different percentage of palm oil clinker substitution with water-cement ratio variation - Walvirus Joseph (School of Environmental Engineering, University Malaysia Perlis, 2013)
This study investigated the effects of substitution of palm oil clinker aggregates in mortar with different water-cement ratio towards the bond strength of brick-mortar masonry which determined by flexural tensile strength.